Ovulation Synchronization For Improving Fertility In Postpartum Dairy Cows - Deshmukh, S.G.; Bakshi, S.A.; Ingawale , M.V.; Chepte , S.D. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A Study was conducted to determine the synchronization response with Ovsynch+CIDR protocol in cows . Pre synchronization medicinal treatment was given to the cows before synchronization. Total 10 cows were synchronized with an intravaginal CIDR containing 558 mg of progesterone for 7 days, starting on day 0 at the time of first GnRh injection. Cows were injected with PGF2α (Cloprostinol, 500 ∝g) IM, on day 7 and the CIDR were removed on day 7 and on day 9 second GnRh injection 2.5 ml I/M was injected. Fixed Time Artificial Insemination was done 16- 24 hr after second GnRh injection. Estrous response was observed 100 per cent. The time required for onset of oestrous was 58.80 ±2.65 hrs., whereas the duration of oestrus observed was 23.80±0.55 hrs. The incidence of intense, intermediate and weak estrus was observed 40 ,40 and 20 per cent, respectively and the first service conception rate was 40 per cent. The Ovsynch+CIDR protocol induces better estrus response and first service conception rate in post partum cows.
Keywords: Synchronization; CIDR; Dairy Cows; Postpartem